2019
DOI: 10.1029/2018gc007978
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Imaging and Physical Properties of the Endeavour Segment: Evidence that Skew Between Mantle and Crustal Magmatic Systems Governs Spreading Center Processes

Abstract: We invert Pg, PmP, and Pn traveltimes from an active‐source, multiscale tomography experiment to constrain the three‐dimensional isotropic and anisotropic P wave velocity structure of the topmost oceanic mantle and crust and crustal thickness variations beneath the entire Endeavour segment of the Juan de Fuca Ridge. The isotropic velocity structure is characterized by a semicontinuous, narrow (5‐km‐wide) crustal low‐velocity volume that tracks the sinuous ridge axis. Across the Moho, the low‐velocity volume ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
52
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 84 publications
8
52
0
Order By: Relevance
“…The disruption of the magma lens between AV1 and AV2 also marks a transition in the lava composition from normal MORB to transitional and enriched MORB. Similar relations between tectonic and magmatic discontinuities have been documented along the EPR (Carbotte et al, , ; Le Saout et al, ; White et al, ), and third‐order tectonic discontinuities have been interpreted to reflect variation in crustal melt volume, which decreases near discontinuities of the magma lens (e.g., Arnoux et al, ; Carbotte et al, ; White et al, ).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The disruption of the magma lens between AV1 and AV2 also marks a transition in the lava composition from normal MORB to transitional and enriched MORB. Similar relations between tectonic and magmatic discontinuities have been documented along the EPR (Carbotte et al, , ; Le Saout et al, ; White et al, ), and third‐order tectonic discontinuities have been interpreted to reflect variation in crustal melt volume, which decreases near discontinuities of the magma lens (e.g., Arnoux et al, ; Carbotte et al, ; White et al, ).…”
Section: Discussionmentioning
confidence: 53%
“…The two larger disruptions of the AML correspond to gaps of magma lenses over distances exceeding 2 km and are directly linked to the locations of the third‐order discontinuities identified in the bathymetry (Figure ). These third‐order discontinuities are also associated with variation in melt content with higher melt content in the center of AV2 evidenced by seismic tomography (Arnoux et al, ). The disruption of the magma lens between AV1 and AV2 also marks a transition in the lava composition from normal MORB to transitional and enriched MORB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This change in the direction of the ridge propagation could be associated with the diminished melt supply to the ridge axis due to the transfer of the Heckle melt anomaly to the east flank 22 . Recently, active-source seismic studies showed that there is a lateral offset between the mantle and the crustal magmatic systems 28,29 (Fig. 1b), which is attributed to the difference in mechanisms of heat transfer that operate in the crust (advection) and mantle (conduction) 29 .…”
mentioning
confidence: 99%
“…Recently, active-source seismic studies showed that there is a lateral offset between the mantle and the crustal magmatic systems 28,29 (Fig. 1b), which is attributed to the difference in mechanisms of heat transfer that operate in the crust (advection) and mantle (conduction) 29 . Interestingly, the most prominent low-velocity zones lie directly beneath the OSCs.…”
mentioning
confidence: 99%